Mosquitoes and their control - Becker, Norbert; Petric, Dusan; Zgomba, Marija; Boase, Clive; Dahl, Christine; Madon, Minoo; Kaiser, Achim (Springer, 2010)
Including a wealth of information on the bionomics, systematics, ecology, research techniques and control of both nuisance and disease vector this readable volume provides practical guidelines and key information for professionals and laymen alike